Relación entre Características Sociodemográficas y Complicaciones Maternas y del Recién Nacido de Parto Domiciliario en Pacientes atendidas en el Hospital Santa Gema de Yurimaguas. Noviembre 2012 – Octubre 2013 - Torres Dávila, Yanira (2014)
The present investigation: relationship between sociodemographic Characteristics and maternal complications and the newborn home Childbirth in patients treated at the Hospital Santa Gema of Yurimaguas. November 2012 - October 2013; quantitative research, and crosssectional Descriptive correlational, with retrospective data collection and Correlational design. The sample is represented by 33 childbirth who were hospitalized in the Service of Obstetrics and Gynecology, complications in the attention of Home childbirth. It was the filling of tabs for the data collection and as an Instrument, the medical histories of the patients served by the Complications of home childbirth; we used the variable sociodemographic Characteristics; for the second variable maternal complications and the Newborn. The data obtained were processed using the chi-square: 36.4 % are ranked equally, 20 to 30 and 31 more years; 84.9 % unmarried; 51.5 % of urban origin. 48.5 % degree of secondary education, 75.8 % Housewife, 21.2 % self-employment; the 45.5 % multiparous emirati Woman delivering, the 39.4 % three living children, 84.8 % have socioeconomic Level equal to or less than 750.00 s/, 57.6 % desired Pregnancy. Tearing in the expulsive were: vaginal tear and cervical Tearing in 21.2 %. Complications in childbirth were 30.3 % placental Retention, 36.4 % other complications. Complications craneoencephalic Newborn: 66.7 % caputsuccedaneum, 18.2 % of brachial plexus injury.In The results indicated that there is significant relationship between Maternal age and maternal tears in the expulsion and brain trauma in the Newborn and between parity to obtain greater Experimental chi square That tabular chi square. In other cases no relationship was found between Variables, that is to say, it was confirmed the null hypothesis.